2018
DOI: 10.3390/brainsci8120203
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of 5-Aminolevulinic Acid Treatment of Glioblastoma by Adding Ciprofloxacin, Deferiprone, 5-Fluorouracil and Febuxostat: The CAALA Regimen

Abstract: The CAALA (Complex Augmentation of ALA) regimen was developed with the goal of redressing some of the weaknesses of 5-aminolevulinic acid (5-ALA) use in glioblastoma treatment as it now stands. 5-ALA is approved for use prior to glioblastoma surgery to better demarcate tumor from brain tissue. 5-ALA is also used in intraoperative photodynamic treatment of glioblastoma by virtue of uptake of 5-ALA and its preferential conversion to protoporphyrin IX in glioblastoma cells. Protoporphyrin IX becomes cytotoxic aft… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 68 publications
1
10
0
Order By: Relevance
“…A total of four compounds (Table 1) were approved by the FDA for the indication glioblastoma. Three of them were therapeutic compounds, one is 5-aminolevulinic acid which is a photo-diagnostic substance for the intraoperative detection of resection margins [11]. These results were in line with the findings of the FDALabel database query: bevacizumab, carmustine, and temozolomide list the indication "glioblastoma" on their FDA approved labels.…”
Section: Approved Drugs For Glioblastomasupporting
confidence: 77%
See 1 more Smart Citation
“…A total of four compounds (Table 1) were approved by the FDA for the indication glioblastoma. Three of them were therapeutic compounds, one is 5-aminolevulinic acid which is a photo-diagnostic substance for the intraoperative detection of resection margins [11]. These results were in line with the findings of the FDALabel database query: bevacizumab, carmustine, and temozolomide list the indication "glioblastoma" on their FDA approved labels.…”
Section: Approved Drugs For Glioblastomasupporting
confidence: 77%
“…A total of four compounds ( Table 1 ) were approved by the FDA for the indication glioblastoma. Three of them were therapeutic compounds, one is 5-aminolevulinic acid which is a photo-diagnostic substance for the intraoperative detection of resection margins [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…Further experimentation on the effect of 5-ALA alone or in combination with other substances or therapies that enhances intracellular PP-IX on tumor cells is required. It has been shown that several compounds, such as vitamin D, ciprofloxacin, deferiprone, and febuxostat, as well as different adjuvant therapies, such as photodynamic therapy and ionizing irradiation, augment the cytotoxicity of 5-ALA in tumoral cells [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, other FDA approved medications increase PpIX accumulation in tumor cells, including iron chelators (deferoxamine and deferiprone), vitamin D, ciprofloxacin, 5-fluorouracil, and febuxostat. Combination of these drugs has been proposed as a means to augment efficacy of 5-ALA in PDT (32).…”
Section: Medications That May Affect Pdt For Glioblastomamentioning
confidence: 99%